2015
DOI: 10.1177/1045159515594155
|View full text |Cite
|
Sign up to set email alerts
|

Information Literacy and Adult Learners

Abstract: Information literacy (IL) skills are essential for adult learners in higher education, especially those unfamiliar with information systems. Citing a lack of literature assessing such skills in adult learners, this article examines the IL abilities of adult learners in an IL course. Using a rubric and annotated bibliographies from study participants, the authors rank the IL abilities of adult students. Similar to studies assessing IL skills in traditional undergraduates, the authors found that adult students s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…Uno de los objetos de estudios de importancia en ALFIN, es las competencias en información de los estudiantes adultos, al respecto, ellos regularmente necesitan más práctica con la evaluación de fuentes de información, mientras que, al completar sus títulos, enfrentan desafíos tales como encontrar, evaluar y utilizar la información como tarea principal, por ello los instructores no deben asumir que estos, tienen competencias informacionales (Rapchak, Lewis, Motyka & Balmert, 2015). Otros de los elementos que se estudian en torno al desarrollo de competencias informacionales en estudiantes adultos, son: la percepción de confianza y motivación para aumentar el compromiso de estos, en intentos de mejorar los niveles de habilidades de gestión de la información mediante el aprendizaje basado en problemas (Roberts, 2017).…”
Section: )unclassified
See 1 more Smart Citation
“…Uno de los objetos de estudios de importancia en ALFIN, es las competencias en información de los estudiantes adultos, al respecto, ellos regularmente necesitan más práctica con la evaluación de fuentes de información, mientras que, al completar sus títulos, enfrentan desafíos tales como encontrar, evaluar y utilizar la información como tarea principal, por ello los instructores no deben asumir que estos, tienen competencias informacionales (Rapchak, Lewis, Motyka & Balmert, 2015). Otros de los elementos que se estudian en torno al desarrollo de competencias informacionales en estudiantes adultos, son: la percepción de confianza y motivación para aumentar el compromiso de estos, en intentos de mejorar los niveles de habilidades de gestión de la información mediante el aprendizaje basado en problemas (Roberts, 2017).…”
Section: )unclassified
“…Por otra parte, ciertos elementos son sugeridos por Twomey (2015) como habilidades cognitivas de orden superior que favorecen el éxito de los estudiantes en la educación superior, estas son: aplicar, analizar y evaluar información. Este último, evaluar la información, también es mencionado en (Rapchak, Lewis, Motyka & Balmert, 2015), donde además de este elemento, se hace referencia a encontrar y analizar recursos adecuados. En este marco, (Faix & Fyn, 2020) analizan, destrezas y habilidades para evitar la desinformación en el complejo entorno medíatico actual, promoviendo el dominio de estrategias para la evaluación de fuentes de información.…”
Section: )unclassified
“…Information literacy is important to adults who access and engage with SDL through online environments, as these adults must learn to make judgments on information quality (Song & Hill, 2007). Research indicated that “information literacy forms the basis for lifelong learning” (Association of Colleges & Research Libraries, 2000, p. 2) as information literacy “includes the ability to ethically and effectively find, access, evaluate, and use information” (Rapchak, Lewis, Motyka, & Balmert, 2015, p. 135). Information literacy skills allow learners to determine the type and quantity of resources needed while effectively and efficiently assessing the information they encounter in a critically manner (Association of Colleges & Research Libraries, 2000).…”
Section: The Tripartite Literaciesmentioning
confidence: 99%
“…Information literacy abilities (ILA) are important for all individuals, from children to adult learners (Rapchak, Lewis, Motyka & Balmert, 2015). Researchers have indicated the importance of skills for retrieving information (Yang, Hwang, & Yang, 2013).…”
Section: Introductionmentioning
confidence: 99%